2020
DOI: 10.3389/fimmu.2020.01287
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly Expressed Embryonic Protein NODAL Alters Breast Cancer Cell Susceptibility to γδ T Cell Cytotoxicity

Abstract: Gamma delta (γδ) T cells kill transformed cells, and increased circulating γδ T cells levels correlate with improved outcome in cancer patients; however, their function within the breast tumor microenvironment (TME) remains controversial. As tumors progress, they begin to express stem-cell associated proteins, concomitant with the emergence of therapy resistant metastatic disease. For example, invasive breast cancers often secrete the embryonic morphogen, NODAL. NODAL has been shown to promote angiogenesis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Several studies have brought evidence of the presence of γδ T cells in the tumor microenvironment of TNBC [ 25 , 32 , 33 , 34 ]. Ma et al previously evaluated the correlations between γδ T cell infiltration and BC characteristics and prognosis in 46 patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have brought evidence of the presence of γδ T cells in the tumor microenvironment of TNBC [ 25 , 32 , 33 , 34 ]. Ma et al previously evaluated the correlations between γδ T cell infiltration and BC characteristics and prognosis in 46 patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they display a strong major histocompatibility complex-independent reactivity against many tumor cell types; they also have no alloreactivity and can be massively expanded from human samples [ 31 ]. Although evidence indicates that γδ T cells have a role in cancer, data on their frequency in cancer tissues and clinicopathological correlates remain scarce, particularly in TNBC, for which only a small number of samples have been analyzed [ 25 , 32 , 33 , 34 ]. Yet, the precise characterization of TNBC stromal components could allow refining the prognostic evaluation and identifying additional targets for immune modulation in this cancer subtype, for which treatments were lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NODAL seems to induce a breast cancer secretome that promotes angiogenesis through regulation of the angiogenic factors platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF) [45] . Furthermore, NODAL expression is inversely correlated with susceptibility to gamma delta (γδ) T cell cytotoxicity, at least in part through decreased surface expression of the immune activating danger signal MHC class I polypeptide-related sequence A/B (MICA/B) [50] . CAFs from a gastric cancer mouse model have recently been shown to promote cancer cell proliferation and resistance to doxorubicin via NODAL secretion [51] and NODAL appears to induce CAF-like phenotypes in mouse and human fibroblast cell lines [52] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have shown that NODAL alters breast cancer cell susceptibility to γδ T cell killing by acting on cancer cells to decrease recognizable antigens on the cell surface. Furthermore, long-term NODAL stimulation reduced Vδ2 T cell antigen receptor expression, suggesting activation of an as-of-yet unidentified signaling pathway in primary γδ T cells50 . We build upon these studies by showing that NODAL may affect TME function and composition directly or indirectly by broadly regulating the breast cancer secretome.…”
mentioning
confidence: 95%
“…For example, NODAL seems to induce a breast cancer secretome that promotes angiogenesis through regulation of the angiogenic factors platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF) 45 . Furthermore, NODAL expression is inversely correlated with susceptibility to gamma delta (γδ) T cell cytotoxicity, at least in part through decreased surface expression of the immune activating danger signal MHC class I polypeptide-related sequence A/B (MICA/B) 50 . CAFs from a gastric cancer mouse model have recently been shown to promote cancer cell proliferation and resistance to doxorubicin via NODAL secretion 51 and NODAL appears to induce CAF-like phenotypes in mouse and human fibroblast cell lines 52 .…”
Section: Introductionmentioning
confidence: 99%